Contested centralisation: Broadcasting rights, legal reform and power struggles in Portuguese football - Gouveia, C. (Sport in Society: Cultures, Commerce, Media, Politics)
This paper analyses the legal reform aimed at implementing a centralised marketing model for audiovisual rights in Portuguese professional football, interpreting it as a politically contested and transformative process. Promoted through legislation as an instrument to correct revenue distribution inequalities among clubs and to enhance competitive balance, the measure translates into a reconfiguration of the institutional, symbolic, and media fields, exposing structural tensions within the Portuguese football ecosystem. Grounded in a qualitative documentary analysis, the study examines the frictions between dominant clubs, regulatory bodies, and media dynamics. Assemblage theory constitutes the central analytical lens, enabling an understanding of how actors, discourses, and dispositifs, in the Foucauldian sense, articulate and reconfigure in contexts of pronounced power asymmetry. The article contributes by conceptualising centralisation as a dynamic relational assemblage, critically demonstrating how reforms oriented towards competitive balance may simultaneously reconfigure and reproduce structural inequalities within the football ecosystem.